Orphan high field superconductivity in non-superconducting uranium ditelluride - Corey E. Frank; Sylvia K. Lewin; Gicela Saucedo Salas; Peter Czajka; Ian M. Hayes; Hyeok Yoon; Tristin Metz; Johnpierre Paglione; John Singleton; Nicholas P. Butch (Nature Communications, 2024)
Abstract Reentrant superconductivity is an uncommon phenomenon in which the destructive effects of magnetic field on superconductivity are mitigated, allowing a zero-resistance state to survive under conditions that would otherwise destroy it. Typically, the reentrant superconducting region derives from a zero-field parent superconducting phase. Here, we show that in UTe2 crystals extreme applied magnetic fields give rise to an unprecedented high-field superconductor that lacks a zero-field antecedent. This high-field orphan superconductivity exists at angles offset between 29o and 42o from the crystallographic b to c axes with applied fields between 37 T and 52 T. The stability of field-induced orphan superconductivity presented in this work defies both empirical precedent and theoretical explanation and demonstrates that high-field superconductivity can exist in an otherwise non-superconducting material.